Restitusi bagi Korban Akibat Tindak Pidana Penganiayaan Berat dalam Perspektif Keadilan - Hasudungan Hutagalung, Henokh; Sudarto, Sudarto (LITERATUS, 2025)
The granting of restitution to victims is in accordance with the principle of restoration to the original state (restutio in integrum), namely an effort that victims of crime must be returned to their original condition before the crime occurred, even though it is based on the fact that it is impossible for the victim to return to their original condition, but at least close to their original condition. The problem is how is the legal regulation of restitution for victims of serious assault crimes? And have the judge's considerations in the South Jakarta District Court Decision Number 297/PID.B/2023/PN JKT.SEL and the DKI Jakarta High Court Decision Number 245/PID/2023/PT DKI provided justice? This research method is normative juridical. The results of the study are (1) The legal regulation of restitution for victims of serious assault crimes is regulated in Supreme Court Regulation Number 1 of 2022 concerning Procedures for Settlement of Applications and Granting of Restitution and Compensation to Victims of Crime. According to researchers, the calculation of Perma Number 1 of 2022 does not correspond to the serious injuries experienced by Child Victim CRYSTALINO DAVID OZORA because it is considered inconsistent with the values of victim justice. (2) The Decision of the DKI Jakarta High Court Number 245/PID/2023/PT DKI has not provided justice for the case of Child Victim Crystalino David Ozora. The Panel of Judges at the South Jakarta District Court only granted the restitution payment imposed on the defendant Mario Dandy of IDR 25 billion. This looks very different from what is contained in the demands of the Public Prosecutor in his prosecution which demanded a sentence for the defendant Mario Dandy of 12 years in prison and restitution to be paid in the amount of IDR 120 billion.